An approach to the external assessment through empirical evidence - Ismael Sanz Labrador; Vicente Alcañiz Miñano (ADIDE Federación, 2015)
This article presents the empiral evidences of standardized evaluations and explores the aspects of such evaluations more interesting to the educational community, and investigates the effects in implementing those exams on the performance of students. Furthermore, it is analyzed the relationship between external evaluations and teaching to the test , it is seen how it affects the introduction of these evaluations in student learning and their performance in international assessments of different characteristics, and the effect it produces in schools located in disadvantaged areas.